Psychotropic polypharmacy impairs walking independence in post-stroke patients. - Matsumoto, Ayaka; Yoshimura, Yoshihiro; Nagano, Fumihiko; Shimazu, Sayuri; Bise, Takahiro; Kido, Yoshifumi; Shiraishi, Ai; Kuzuhara, Aomi; Hamada, Takenori; Yoneda, Kouki (European Journal of Clinical Pharmacology, 2025)
Purpose: Psychotropic drugs are associated with adverse outcomes in older adults. However, evidence on the effect of psychotropic use on walking ability in post-stroke patients is lacking. This study examined the association between psychotropic medication use and walking independence in post-stroke patients. Methods: This retrospective cohort study included stroke patients admitted for convalescent rehabilitation at a Japanese hospital between 2020 and 2022. Psychotropic medications (benzodiazepines, hypnotics, antipsychotics, and antidepressants) prescribed at admission were recorded. The primary outcome was walking independence at discharge, defined as a Functional Independence Measure (FIM) walk score ≥ 6. Logistic regression analyses examined the association between the number of psychotropic drugs and walking independence, adjusting for potential confounders. Results: Of the 709 patients enrolled, 559 (mean age 75.5 years, 52.8% male) were included in the analysis. At admission, 25.4% of patients used psychotropic drugs. In the adjusted analysis, the number of psychotropic medications was independently associated with lower walking independence at discharge (OR 0.620, 95% CI 0.428–0.897, P = 0.011). Hypnotic use specifically showed a negative impact on walking independence (OR 0.331, 95% CI 0.154–0.708, P = 0.004). However, psychotropic drug use was not significantly associated with improvement in FIM-motor scores. Conclusion: Psychotropic polypharmacy at admission, particularly with hypnotics, was associated with reduced likelihood of achieving walking independence after stroke rehabilitation. Judicious use of psychotropic medications may be warranted when ambulation is a critical goal for older post-stroke patients.